A morte inventada e Borrando a papá : cinema, paternidade e alienação parental - Pinto, Débora Wagner (2019)
This dissertation aims to study paternity in Parental Alienation, in the narrative context of the documentaries A morte inventada (2009), national production, by Alan Minas, and Borrando a papá (2014), argentine production, by director Ginger Gentile and Sandra Fernández Ferreira. The text shows how paternity is characterized in Parental Alienation and also its representation in the documentaries mentioned above. In addition, we enter the Law, as well as its laws regarding the analyzed subject. We reflect on paternity in these three areas: Cinema, Psychology and Law seeking to understand the gender issues in the family, the behaviors of the alienating parent and the alienant in Parental Alienation. Finally, we identify documentary productions as self-representations, which through social actors represent the director's paternity, in the case of A morte inventada, and the producer’s, in Borrando a papá, as alienated parents in the context of Parental Alienation. It is evident in both documentaries that the paternal figure presents itself as alienated and it is intensified in the narratives of parents and children regarding the consequences of the Parental Alienation.